Sistem Informasi Kepegawaian Berbasis Web Pada Dinas Energi Dan Sumber Daya Mineral Provinsi Jambi - Sari, Artika; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2022)
The Department of Energy and Mineral Resources (ESDM) of Jambi Province, is a service that handles various mining problems, this service is addressed at Jalan Arief Rachman Hakim No. 30 Telanaipura Jambi, Simpang IV Sipin Village, Telanaipura District. Problems in the data processing process, namely the process of finding data at a slow value, the data does not appear automatically so it must input repeatedly, and data cannot be mutually integrated due to the absence of a database. The benefits of the research conducted are improving performance in the admin section so that it can simplify employee data processing. The purpose of the study is to design a Staffing Information System at the Jambi Province Energy and Mineral Resources Office. The method of using the prototype model, the results of the research are data processing applications that have been designed to facilitate data processing and report generation. Suggestions before using the application, it is better for the user to get training first so that they can be operated optimally